Modelling, Design and Validation of Spatially Resolved Reflectance Based Fiber Optic Probe for Epithelial Precancer Diagnostics - Pankaj Singh (Applied Sciences, 2020)
Fiber-optic probes are imperative for in-vivo diagnosis of cancer. Depending on the access to a diseased organ and the mutations one aims to sense, the probe designs vary. We carry out a detailed numerical study of the efficacy of the common probe geometries for epithelial cancer characterization based on spatially resolved reflectance data. As per the outcomes of this comparative study, a probe has been manufactured and using Monte Carlo look up table based inversion scheme, the absorption and scattering coefficients of the epithelium mimicking top layer have been recovered from noisy synthetic as well as experimental data.